The Position of LGBT in the Hadith Perspective: Between Normative Rigidity and Human Rights Challenges in Indonesia - Mosiba, Risna; Ahmad, La Ode Ismail; Sakka, Abdul Rahman; Djafri, Muh. Taufan; Fatmal, Abd. Bashir (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
From an Islamic perspective, the phenomenon of Lesbian, Gay, Bisexual, and Transgender (LGBT) has become a controversial issue in social and religious studies. In Islamic history, LGBT behaviour is often associated with the story of the Prophet Luth people who were punished for their actions. On the other hand, modern human rights emphasise the im-portance of non-discrimination against LGBT people. This study examines hadiths related to LGBT and their relevance in the social and legal context in Indonesia. This study used a qualitative approach with a library research method, collecting data from primary sources such as prophetic traditions, and secondary sources such as books of interpretation, aca-demic journals, and scientific articles. The results show that the traditions related to LGBT have variations in Sanad and Matan, which shows differences in opinion regarding its validity among hadith scholars, causing differences in the interpretation of Islamic law. Many scholars classify LGBT behaviour as prohibited, although there are differences in the punishments given. The novelty of this research lies in the in-depth analysis of LGBT-related traditions by considering aspects of Islamic law and human rights in the Indonesian context. The academic implication of this study is that it provides new insights into the-matic hadith studies, particularly in response to contemporary social issues, particularly LGBT with Islamic law.